2010
DOI: 10.3354/meps08600
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between allochthonous subsidy input and isotopic variability in the giant kelp Macrocystis pyrifera in central California, USA

Abstract: Isotope values of primary producers can vary greatly across space and time due to changes in physiological status and the source of subsidies used in photosynthesis. Forests of the giant kelp Macrocystis occur in temperate oceans around the world and are positioned at the land -sea interface where they may receive subsidies from terrestrial and open ocean sources. In this study, we investigated the spatial and temporal variability in δ 13 C and δ 15 N values of M. pyrifera over 3 yr in Big Sur, California, USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…For P. oceanica, the maximum photosynthetically active radiation above their canopies ranged from 50 to 310 mmol m −2 s −1 between the sampling locations and the coverage of leaf necrosis ranged from 0 to 37.5%. M. pyrifera samples were collected either in spring or late fall, periods of contrasting ocean conditions that result in widely divergent bulk isotopic values [18]. Note that our sampling was not designed for investigating the influence of geographical region on terrestrial plants since a previous study [14] found no systematic differences in δ 13 C AA patterns from greenhouse plants and those collected in boreal and mangrove ecosystems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For P. oceanica, the maximum photosynthetically active radiation above their canopies ranged from 50 to 310 mmol m −2 s −1 between the sampling locations and the coverage of leaf necrosis ranged from 0 to 37.5%. M. pyrifera samples were collected either in spring or late fall, periods of contrasting ocean conditions that result in widely divergent bulk isotopic values [18]. Note that our sampling was not designed for investigating the influence of geographical region on terrestrial plants since a previous study [14] found no systematic differences in δ 13 C AA patterns from greenhouse plants and those collected in boreal and mangrove ecosystems.…”
Section: Methodsmentioning
confidence: 99%
“…The terrestrial plant collection was supplemented with two species from public owned land in Denmark where no permission was required for sampling. We obtained five P. oceanica samples from the Catalonian shore in the Mediterranean Sea under a permit to Teresa Alcoverro by the Catalan Water Agency, and the five M. pyrifera samples from the Californian shore were sampled under a permit to Melissa M. Foley [18] by NOAA’s Monterey Bay National Marine Sanctuary. All field samples were kept on crushed ice in coolers and stored between 1 and 3 days before thoroughly washing them in milliQ water (except for animal and seston samples).…”
Section: Methodsmentioning
confidence: 99%
“…There are reports that the latter is highly variable among individuals, and even within a single blade (Stephenson et al 1984, Dunton & Schell 1987. For a given macroalgal species, the isotope signature can be affected by many factors such as depth, light partitioning, and nutrient availability (Foley & Koch 2010, Hepburn et al 2011. Although active tidal hydrodynamics most likely prevent nutrient limitation in the Roscoff area (Wafar et al 1983), light levels may have influenced the isotopic signal because high variation in light is expected particularly in kelp forest strata (Norton et al 1977 Senescent red algae associated with the kelp forest appeared to decay in November until new growth commenced before March and continued to June-September.…”
Section: Organic Matter Sources Of the Kelp Forestmentioning
confidence: 99%
“…the exact diet of the simulated consumer); and (2) the standard assumptions were used (the model is given fresh macrophyte isotope values as potential food input data). 'Fresh' Saccharina was represented by Week 1 scraped blades, as 'fresh' samples are frequently scrubbed or scraped and then rinsed to remove epibionts (Guest et al 2008, Page et al 2008, Foley & Koch 2010. Fresh Saccharina was verified as isotopically distinct from all other sources before the analysis ( Table S3 in the Supplement at www.intres.com/articles/suppl/m494p107_supp.…”
Section: Model Sourcesmentioning
confidence: 99%